(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The purpose of this study is to assess the operation of micro-businesses in terms of profile, operational status, and SWOT analysis. The results of this study reveal that the profile of micro-businesses in Novaliches Bayan, Quezon City, is below 50,000 for Starting capital, 5,000 – 10,000 for monthly income, and 15,000 - 20,000 for monthly expenses, which belong to food, beverage and the tobacco industry. Micro-business owners are hands-on in the operation and consider the accessibility of the location and where a lot of people pass by. Micro businesses adopt the latest technology because it’s what the business uses for posting or promoting products and services. Technology is a big help in selling products to gain more profit and increase sales. Micro businesses utilize the equipment for kitchen utensils, stoves, dining sets, cooking equipment, and grillers by regularly checking it for small repairs and defects. Owners select employees based on how hardworking and trustworthy they are, choosing employees who are good at selling, marketing, communicating, and negotiations. Micro businesses assess the SWOT analysis in terms of strengths as their loyal customers, weaknesses as store/service capacity, and opportunities as creating more loyal customers. The threats are seasonal demand; the rainy season and summer are different. This study recommended that micro businesses should monitor their financial projections and save money to innovate products for more sustainable income. Owners should invest in modern equipment continue to maintain a good relationship with customers, and use that as a marketing tool for promoting the business. Owners must try to put the presence of their business online. Micro businesses should also use delivery services to fill the lack of store/service capacity and must adapt to trend products during rainy, summer seasons or seasonal demands.